2013
DOI: 10.1136/bjsports-2012-091988
|View full text |Cite
|
Sign up to set email alerts
|

Injury initiates unfavourable weight gain and obesity markers in youth

Abstract: Objective The purpose of this study was to examine the association of knee injuries with subsequent changes in body mass index and body composition during maturation in young females. Methods A prospective longitudinal study design was employed to evaluate young females active in soccer or basketball (N=862). Participants who completed at least 1-year follow-up to provide consecutive annual measures of BMIZ and %fat were included in the study analysis to determine the effect of knee injuries on the trajector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 40 publications
2
43
1
Order By: Relevance
“…19 Longitudinal data indicate knee pain and injury influences an immediate increase in BMI z-score and body fat percentage in the year of reported incidence. 88 Future research should focus on determination of the underlying pathomechanics of PFP that increase its prevalence in young growing girls to development of sex-specific and age-appropriate interventions. Based on the current report it may be speculated that effective interventions implemented at an early age could be beneficial to prevent PFP prevalence and potentially reduce future risk of ACL injury.…”
Section: Discussionmentioning
confidence: 99%
“…19 Longitudinal data indicate knee pain and injury influences an immediate increase in BMI z-score and body fat percentage in the year of reported incidence. 88 Future research should focus on determination of the underlying pathomechanics of PFP that increase its prevalence in young growing girls to development of sex-specific and age-appropriate interventions. Based on the current report it may be speculated that effective interventions implemented at an early age could be beneficial to prevent PFP prevalence and potentially reduce future risk of ACL injury.…”
Section: Discussionmentioning
confidence: 99%
“…Regular participation in physical education, sports and well-designed fitness programmes that integrate both health-related and skill-related fitness components may provide a mechanism to develop dynamic interceptive actions and to increase physical activity levels in youth 65 66. In sports such as baseball, for example, being able to field an infield ground ball without being distracted by a runner on base can decrease injury risk as well as enhance motor skill performance 67.…”
Section: The Importance Of Timing Of Brain Development—window Of Oppomentioning
confidence: 99%
“…As youth engage earlier in formal-ized sport and specialize in sport(s) at younger ages, they may be at increased risk of experiencing overuse injury ( 45). Of concern, is researchers have shown that the cycle of reduced activity after an acute injury can initiate overweight and obesity markers in youth ( 85).…”
Section: Problem 3: Early Sport Specializationmentioning
confidence: 99%